Development and validation of the Nutrition Care Process Assessment of Brief Level of Expertise screening tool - LaBonte, Luc R.; Papoutsakis, Constantina; Lewis, Sherri; Colin, Casey (Frontiers in Nutrition, 2025)
ObjectiveTo develop and validate an abbreviated screening tool to screen Nutrition Care Process (NCP) proficiency.MethodsThe questionnaire was developed using existing literature. All iterations were reviewed by subject matter experts. The questionnaire underwent several methods of testing, including content validity, face validity, internal consistency reliability, and test–retest reliability. Questions were scored based on answer selection, and participants were categorized by observed levels of proficiency.ResultsInternal consistency reliability testing indicated removal of two items, creating a 3-item questionnaire (the NCP Assessment of Brief Level of Expertise, or NCP-ABLE). All items met content (S-CVI = 0.94) and face (S-FVI = 0.94) validity and internal consistency (α = 0.75) and test–retest (r = 0.8, p = 0.009, 95% CI: 0.274, 0.962) reliability thresholds. Six (85.7%) of the subject matter experts reported higher degrees of proficiency with scores of 3 (highest quartile placement), whereas one expert demonstrated lower levels of proficiency through the score of 1 (second quartile placement).ConclusionThe NCP-ABLE met the established validity and reliability thresholds. This supports its utilization as a screen for NCP proficiency, particularly to identify individuals demonstrating lower levels of NCP knowledge proficiency. The NCP-ABLE may be effective for the screening of clinicians, educators, preceptors, and students for educational intervention or quality improvement initiatives. Future investigations may aim to validate the NCP-ABLE in other languages. Further research is needed to determine the relationship between NCP-ABLE scores and NCP implementation, possibly by comparing NCP-ABLE results and scores from robust assessments of NCP practice.